A pH-responsive crosslinker platform for antibody-drug conjugate (ADC) targeting delivery. Issue 75 (31st August 2022) - Migliorini, Francesca; Cini, Elena; Dreassi, Elena; Finetti, Federica; Ievoli, Giovanni; Macrì, Giulia; Petricci, Elena; Rango, Enrico; Trabalzini, Lorenza; Taddei, Maurizio
Abstract : Gallic acid, a key component of red wine tannins, has been transformed into a linker that releases Doxorubicine or Combretastatin A4 at pH 5.5 in cancer cells. Abstract : We report a new 1–6 self-immolative, traceless crosslinker derived from the natural product gallic acid. The linker acts through a pH-dependent mechanism for drug release. This 5-(hydroxymethyl)pyrogallol orthoester derivative (HMPO) was stable for 24 hours at pH values of 7.4 and 6.6 and in plasma, releasing molecules bound to the hydroxymethyl moiety under acid-dependent stimuli at pH 5.5. The linker was non-toxic and was used for the conjugation of Doxorubicin (Doxo) or Combretastatin A4 with Cetuximab. The ADCs formed showed their pH responsivity reducing cell viability of A431 and A549 cancer cells better than Cetuximab alone.